2001
DOI: 10.1159/000046040
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Imaging Changes in Patients with Chronic Renal Failure Treated Conservatively or in Hemodialysis

Abstract: Background: Nonuremic patients with apparently normal memory and behavior, studied by means of cerebral computed tomography and found to have cerebral atrophy (CA), evidenced functional intellectual deficits when they underwent psychometric testing. The finding of CA has been repeatedly reported in limited case groups of uremic patients who also demonstrated functional intellectual deficits on the basis of the same tests. This retrospective study considered all diagnostic cerebral computed tomography scans don… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 19 publications
3
47
0
2
Order By: Relevance
“…Moreover, global loss of GM was associated with longer duration of hemodialysis treatment. Our atrophy findings corroborate previous reports (Vorstrup et al, 1992;Burn and Bates, 1998), and the relationship with longer duration of hemodialysis treatment is also consistent with other works (Savazzi et al, 1995(Savazzi et al, , 2001Kamata et al, 2000). We also found focal increase in CSF density in suprapontine areas of the midbrain, adjacent to, but not clearly identical to, the pontine changes seen in osmotic demyelination syndrome (Tarhan et al, 2004); none of our patients were documented to show clinical symptoms consistent with that syndrome, but they were not specifically assessed for this purpose and we cannot exclude this possibility.…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, global loss of GM was associated with longer duration of hemodialysis treatment. Our atrophy findings corroborate previous reports (Vorstrup et al, 1992;Burn and Bates, 1998), and the relationship with longer duration of hemodialysis treatment is also consistent with other works (Savazzi et al, 1995(Savazzi et al, , 2001Kamata et al, 2000). We also found focal increase in CSF density in suprapontine areas of the midbrain, adjacent to, but not clearly identical to, the pontine changes seen in osmotic demyelination syndrome (Tarhan et al, 2004); none of our patients were documented to show clinical symptoms consistent with that syndrome, but they were not specifically assessed for this purpose and we cannot exclude this possibility.…”
Section: Discussionsupporting
confidence: 93%
“…Further studies are needed to understand the pathophysiology, prevention, and treatment of cerebrovascular disease in ESRD, with additional focus on subclinical disease, including cognitive function (37), cerebral white matter changes (38), and subclinical strokes (39), as well as imaging techniques with magnetic resonance imaging to earlier identify cerebrovascular disease. inga, Neil Powe, Dr. Renuka Sothinathan, Dr. Richard Ugarte, Dr. Gayanne Yenokian, and Paige Armstrong.…”
Section: Discussionmentioning
confidence: 99%
“…32 It was subsequently shown in such patients that the lesions were prominent in the frontal lobes and were correlated with the duration of hemodialysis. 33,34 Other markers or risk factors for potential cerebrovascular disease, such as SBIs, have also been reported. Cusmano and Savazzi showed that 10% of CKD patients, most of whom were undergoing hemodialysis, had SBIs.…”
Section: Brain Lesions In Ckd Patientsmentioning
confidence: 99%